Euro-Atlantic Integration of Macedonia and the Name Issue: Viewed from the Prism of Albanians - Azizi, Abdula (Richtmann Publishing, 2012)
Relying on the fact that Macedonia since its independence has been faced with various challenges in the path of Euro-Atlanticintegration of the country, and as one of the main challenges still remains the name dispute resolution with Greece. In this regard, wenotice that the political parties but especially the citizens do not have a common standpoint on this issue. In fact, the opposite extremepositions that have built communities on how to resolve the aforementioned dispute increase the gap between them. Precisely, in thispaper dilemmas will be shown about the Euro-Atlantic future of Macedonia concerning the resolution of the dispute with the state name,seen from the standpoint of citizens. In particular, it will analyze the empirical data arising from the survey conducted with the citizens ofthe Albanian community in Macedonia, about their beliefs on the state name dispute resolution - as an obstacle to Euro-Atlanticintegration of the country. I believe that the results of this paper will give to the political subjects a clearer picture on the attitudes ofcitizens on this issue, especially those representing the Albanian community in the Macedonian government.